On the predictability of turbulent fluxes from land: PLUMBER2 MIP experimental description and preliminary results - G. Abramowitz; G. Abramowitz; A. Ukkola; A. Ukkola; S. Hobeichi; S. Hobeichi; J. Cranko Page; J. Cranko Page; M. Lipson; M. G. De Kauwe; S. Green; S. Green; et al. (Biogeosciences)
Accurate representation of the turbulent exchange of carbon, water, and heat between the land surface and the atmosphere is critical for modelling global energy, water, and carbon cycles in both future climate projections and weather forecasts. Evaluation of models' ability to do this is performed in a wide range of simulation environments, often without explicit consideration of the degree of observational constraint or uncertainty and typically without quantification of benchmark performance expectations. We describe a Model Intercomparison Project (MIP) that attempts to resolve these shortcomings, comparing the surface turbulent heat flux predictions of around 20 different land models provided with in situ meteorological forcing evaluated with measured surface fluxes using quality-controlled data from 170 eddy-covariance-based flux tower sites.